Barriers to Computed Tomography Radiation Risk Communication in the Emergency Department: A Qualitative Analysis of Patient and Physician Perspectives. (February 2014) - Robey, Thomas E.; Edwards, Kelly; Murphy, Mary K.; Theodoro, Daniel L.
Abstract Objectives This qualitative study aimed to characterize the barriers to informed discussions between patients and emergency physicians (EPs) about radiation risk from computed tomography (CT) and to identify future interventions to improve patient understanding of CT radiation risk. Methods This study used a focus group approach to collect concepts about radiation risk exposure from a national sample of EPs and a local sample of emergency department (ED) patients. A directed content analysis used an a priori medical ethics framework to explore themes from the focus groups while a subsequent normative ethics analysis compared these results with existing perceptions about discussing CT radiation risk. Results Focus groups (three each for a total of 19 EPs and 27 patients) identified concepts consistent with core medical ethics principles: patients emphasized autonomy and nonmaleficence more than physicians, while physicians emphasized beneficence. Subjects' knowledge of radiation dose and risk were equivalent to previously published reports. When asked about whether they should talk about radiation with patients, 74% of EPs reported that radiation exposure should be discussed, but the study EPs self‐reported doing so with only an average of 24% of patients. Patients reported wanting to hear about radiation from their physicians the next time they need CT scans and thought that a written handout would work better than any other method. When presented with options for how to discuss risk with patients, EPs reported needing easy access to risk information and preferred discussion over other communications approaches, but had mixed support of distributing patient handouts. Conclusions The normative view that radiation from diagnostic CT should be discussed in the ED is shared by patients and physicians, but is challenged by the lack of a structured method to communicate CT radiation risk to ED patients. Our analysis identifies promising interest among physicians and patients to use information guides and electronic order prompts as potential informational tools to overcome this barrier.